Advancing AI Adoption in the Public Sector: Toward Hybrid Intelligence with Stakeholder Perspectives - Liu, Helen K.; Musiatowicz-Podbiał, Grażyna; Tseng, Hsien-Lee; Ko, Wei-Jan; Ciesielska, Magdalena (Conference on Digital Government Research, 2025)
Governments are increasingly adopting AI to improve public services as part of smart city development, and hybrid intelligence plays an essential role in this developmental process. This panel, emphasizing stakeholder perspectives, explores the opportunities and challenges of adopting hybrid intelligence for smart city development. We include three papers and six authors for the panel. The first paper investigates how smart city initiatives facilitated through citizen-government participation platforms differ in terms of stakeholder groups, types of participation, and technology employed. The second paper examines how the municipal city, Hsinchu City Government, utilizes intersection fisheye camera images to analyze traffic flow and their related stakeholders' views on such adoption. The last study examines data-driven public services by combining the strengths of human experiences and artificial intelligence. This paper discusses studies utilizing open data, big data, or linked data to support informed decision-making through an inclusive process and inter-governmental collaboration and innovation transfer, as shown in the second paper. The panel will also reserve time for the audience to join the discussions and share their related research in applying hybrid intelligence for smart city development.